Praktikum Akuntansi dalam Persepsi Mahasiswa Pendidikan Ekonomi Universitas Sriwijaya - Yuliana FH; Siti Fatimah; Dewi Pratita; M. Bintang Respati; Deva Oktapiani (SAP (Susunan Artikel Pendidikan), 2026)
This study aims to obtain an overview of the perceptions of students of the Economics Education Study Program at Sriwijaya University regarding the implementation of accounting practicum learning. The research method used was descriptive quantitative, with a population of 154 students and a saturated sampling technique. The research instrument used was a questionnaire compiled based on four aspects, including (1) the characteristics of the accounting practicum course; (2) obstacles to implementing accounting practical learning; (3) need for digital accounting practical books; (4) Competency analysis and learning outcomes. Based on the research conducted, a picture of student perceptions was obtained, namely that this course is very popular with students because it supports their competence as future accounting and economics teachers. In addition, various learning obstacles were still encountered, such as limited use of computers and accounting applications, basic understanding of accounting, learning time, material complexity, and creative and diverse teaching resources. Therefore, 43.5% of students strongly agreed, and 56.5% agreed that they needed creative learning resources in the form of digital accounting practicum books that could guide accounting practicum activities.